Pathogenic mechanisms of Aeromonas hydrophila and the protective role of probiotics in sustainable aquaculture - Gelana Urgesa Ayana; Mukhtar Muhammad Abdullateef; Gazahegn Wakjira Yadata; Rehan Manzoor; Sahr Lamin Sumana; Abate Melaku Gelata; Md Mohidul Islam (Archives of Microbiology, 2026)

Phytochemical-rich extract of Psidium guajava ameliorates letrozole-induced PCOS in female rats by modulating the NF-κB inflammatory pathway - Hao Xu; Palwasha Haider; Majid Manzoor; Rida Siddique; Hina Manzoor; Muhammad Yasir Ali; Rizwan Rashid Bazmi; Liaqat Hussain; Ping Wang (Tissue and Cell, 2026)

Red pepper seed protein isolate: Pulsed electric field assisted modification to improve its structural and functional properties - Murtaza Ali; Xin-An Zeng; Muhammad Faisal Manzoor; Isam A. Mohamed Ahmed; Muhammad Waseem (Innovative Food Science & Emerging Technologies, 2026)

Solar radio flux F10.7 forecasting via deep learning: A hybrid approach with LSTM and GRU - Mohsin Ghaffar Ghouri; Muhammad Umair; Manzoor Ahmed Hashmani (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Artificial intelligence integrated in non-destructive technologies for monitoring food freshness: A review of next generation approach - Muhammad Waseem; Muhammad Rizwan Javed; Muhammad Faisal Manzoor; Xiuqi Xia; Yilei Huang; Xiaomei Chen (Food Research International, 2026)

Nanopriming with biogenic selenium nanoparticles restores physiological performance and antioxidant defense in salt-stressed maize cultivars - Hummera Nawaz; Amina Ameer; Ameer Khan; Anees Manzoor; Muhammad Jamil; Saima Shafique; Ansar Mehmood; Khawaja Shafique Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Biological and synthetic biology strategies for polystyrene degradation: mechanisms, microbial advances, and circular economy perspectives - Mehar Nazir; Asma Rehman; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Manahil Akmal; Ghazala Iram; Faiza Manzoor; Sadia Aziz; Muhammad Shehroz Zafar; Muhammad Adnan Iqbal (Biodegradation, 2026)

In silico identification of novel PTP1B inhibitors by the investigation of molecular mechanism, QSAR, and DFT studies - Humaira Zulfiqar; Samira Akter; Jarin Tasnim; Muhammad Younis; Md. Mehedi Hasan; Sidra Manzoor; Sarnop Sarker; Muhammad Waqas; Khan Rajib Hossain (In Silico Pharmacology, 2026)
Protein tyrosine phosphatase 1B (PTP1B) is a well-known and promising drug target involved in the negative regulation of insulin and leptin signaling, and new anti-diabetic molecules for the treatment of type 2 diabetes are directly in its hands. A series of PTP1B inhibitors was discovered and characterized using in silico techniques, including virtual screening, molecular docking, ADMET profiling, toxicity prediction, VEGA-QSAR analysis, molecular dynamics (MD) simulation, and density functional theory (DFT) calculations. A starting library of 1000 anti-diabetic compounds was screened, and PubChem CID 44560696 was identified as the most successful hit. The most potent inhibitor was then identified as CID 44560744 through chemical analogy-based refinement, with a binding free energy of − 9.13 kcal/mol and the ability to form several stabilizing hydrogen bonds and hydrophobic interactions with the key catalytic residues. DFT-optimized geometry and docking revealed that the lead compound shows high stability and strong PTP1B inhibition, showing superior binding affinity compared to ursolic acid, which exhibited a lower binding energy of − 6.34 kcal mol −1 . The MD simulations showed that the PTP1B-ligand complex was structurally stable and compacted during the 200 ns simulation, with desirable profiles for RMSD, RMSF, Rg, SASA, and hydrogen bonds. The DFT and FMO analyses indicated that the compound exhibits extreme chemical reactivity and electron-transfer capability, owing to its low HOMO-LUMO gap, high softness, and moderate electrophilicity. The results of ADMET and toxicity evaluations (SwissADME, ProTox-II, and VEGA-QSAR) pointed to satisfactory solubility, non-carcinogenicity, no mutagenicity, and high pharmacological safety. Overall, the synergy of the computational methods has made CID 44560744 a lead scaffold for the development and optimization of selective PTP1B inhibitors for T2DM therapy.

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Synergistic effects of pulsed electric field and ultrasound on microstructure and bioactive properties of fresh and old ginger juice - Zhong Han; Wenhao Xiao; Ji Ma; Muhammad Mohsin Raza; Xin-An Zeng; Muhammad Faisal Manzoor; Muhammad Talha Afraz (Journal of Food Engineering, 2026)

Synthesis of Novel Bentonite Composites for Enhanced Remediation of Basic Fuchsin Dye - Ayesha Naseer; Ruba Munir; Gadah Albasher; Muhammad Husnain Manzoor; Murtaza Sayed; Faheem Abbas; Saima Noreen (Water, Air, & Soil Pollution, 2026)

Strigolactone-mediated regulation of chromium uptake, redox homeostasis, and photosynthetic carbon metabolism during Cr (VI) stress tolerance in Capsicum annuum L. - Kaiser Iqbal Wani; Huazheng Shao; Yingsai Li; Muhammad Aamir Manzoor; Huizhen Fu; Xu Lu; Shanhan Cheng; Javaria Tabusam; Tariq Aftab; Zhiwei Wang (Plant Cell Reports, 2026)

Mycoviruses against plant pathogenic fungi: current understanding and future avenues of their potential implication - Fatima Mukhtar; Noor Fatima; Sawera Manzoor; Iqbal Ahmad Alvi; Shafiq ur Rehman; Muhammad Asif (Archives of Microbiology, 2026)

Enhanced Antimicrobial Photodynamic Effect Against Escherichia coli Using MXene-Based Silver–Curcumin 2D Nanocomposite Photosensitizers - Saliha Noor; Shahzad Anwar; Rafaqat Ali Khan; Sawera Malik; Hina Ali; Farwa Nurjis; Shaista Taimur; Muhammad Iftikhar; Muhammad Saleem; Babar Manzoor Atta (Journal of Fluorescence, 2026)

Structure-based virtual screening, molecular dynamics and MM-PBSA/GBSA analysis for the identification of novel CDK6 inhibitors against prostate cancer - Manzoor Ahmad; Muhammad Ajmal Khan; Ashraf Ullah Khan; Sadia Butt; Yahya Khan; Amir Zeb; Nadia Bibi; Aishma Khattak; Hina Ahsan; Ajaz Ahmad; Amin Ullah (In Silico Pharmacology, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Evolutionary insight and characterization of WOX genes in callus development and differentiation of Peucedanum praeruptorum - Cheng Song; Haoyu Pan; Muhammad Arif; Haiyu Wang; Yunpeng Cao; Bangxing Han; Muhammad Aamir Manzoor (Planta, 2026)

Molecular insights into HPV-16 L2 capsid protein and inhibitor screening study - Saima Younas; Atiqa Nosheen; Muhammad Abdul Qayyum; Hafiza Ayesha Malik; Sadia Manzoor; Rabia Arooj; Nazim Hussain; Qurban Ali; Muhammad Arshad Javed; Daoud Ali; Adnan Iqbal (In Silico Pharmacology, 2026)

Combined application of 5-ALA and nitric oxide improves lead detoxification and antioxidant defense in barley - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Wael Elmenofy; Muhammad Aamir Manzoor; Rashid Iqbal (Biodegradation, 2026)

Silver nanoparticles in water disinfection: a comprehensive overview on their mechanisms, benefits, and limitations - Muhammad Shehroz Zafar; Sana Ejaz; Farhan Ahmad; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Faiza Manzoor; Sadia Aziz; Saima Iqbal; Muhammad Adnan Iqbal (Archives of Microbiology, 2026)

Artemisia absinthium attenuates hepatic fibrosis in mice by suppressing hepatic stellate cells activation and modulating inflammatory chemokine signaling - Rabbia Manzoor; Iram Gull; Abrar Ahmed; Tuba Ghulam Hussain; Ubaida Hussain; Muhammad Shahbaz Aslam (Cell Biochemistry and Biophysics, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Exploring the efficacy of a novel cannabidiol and bevacizumab combination in non-small cell lung cancer - Abdul Qadir; Zurqa Khalid; Ayesha Kashmala Ghauri; Muhammad Hamza Dawood; Usama Manzoor; Habib Ur Rehman (DARU Journal of Pharmaceutical Sciences, 2026)

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Synergistic effect of Clupea harengus by-product hydrolysates and kappa carrageenan mixture on oxidation prompted structural alterations in Clupea harengus proteins during frozen temperature variations - Noman Walayat; Piotr Kulawik; Asad Nawaz; Isam A. Mohamed Ahmed; Muhammad Faisal Manzoor; Zhucheng Su; Ran Wei (Food Hydrocolloids, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Graph-based and molecular modeling approaches to identify TpiA as a noval therapeutic target in Neisseria meningitidis - Sana Abdul Ghaffar; Iqra Muneer; Irfan Manzoor; Roba M. S. Attar; Nada A. Alzunaidy; Basmah F. Alharbi; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem; Muhammad Tahir ul Qamar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Arginine-Dependent Defense Actions in Rice (Oryza Sativa L.) Against Microplastic Contaminated Root Zone - Modhi O. Alotaibi; Naila Hadayat; Mohamed O. Alshahrani; Muhammad Kashif Irshad; Anees Manzoor; Nahaa M. Alotaibi; Fahad Mohammed Alzuaibr; Suliman Mohammed Suliman Alghanem; Omar Mahmoud Alzoubi; Jeddi Kaouthar; Saher Nawaz (Journal of Soil Science and Plant Nutrition, 2026)

Modelling adoption of camera-based safety monitoring systems in construction: an extended technology acceptance model approach using PLS-SEM - Nawal Manzoor; Hilal Khan; Muhammad Usman Hassan; Khursheed Ahmed; Muhammad Umer Zubair (Innovative Infrastructure Solutions, 2026)

Efficient De Novo Assembly and Recovery of Microbial Genomes from Complex Metagenomes Using a Reduced Set of k-mers - Hajra Qayyum; Muhammad Faheem Raziq; Haseeb Manzoor; Syed Shujaat Ali Zaidi; Amjad Ali; Masood Ur Rehman Kayani (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Ecological Niche Overlap and Environmental Associations Among Species of the Morchella (Morchellaceae, Pezizomycotina) From P.R. China - Akmal Muhammad; Yinglian Deng; Syed Amir Manzoor; Changlin (Charlie) Zhao (New Zealand Journal of Botany, 2026)
Morchella species, economically significant edible fungi, are affected by numerous environmental factors; however, details concerning their ecological niche are poorly understood. Consequently, this study aims to fill this deficiency by applying a modeling approach to the fundamental niche of the Morchella genus, incorporating species from the elata and esculenta clades. In this work, we examined the distribution patterns of Morchella species in relation to significant environmental factors. The MaxEnt algorithm was utilized to conclude habitat validity. The environmental variables incorporated into the final models comprised isothermality, temperature seasonality, maximum temperature of the warmest month, mean temperature of the warmest quarter, precipitation of the wettest month, precipitation seasonality, slope, and aspect. The PCA‐env analysis revealed that the first two axes accounted for 69.55% of the overall variation in climatic conditions across the ranges of the two clades (PC1 = 41.36% and PC2 = 28.19%). An analysis and comparison of the climatic space engaged by the two primary clades, along with their overlap, were conducted. These findings emphasized the utility of ecological niche modeling for understanding how climatic conditions can influence the dispersal of Morchella clades. These results aid in formulating enhanced conservation strategies and in informed decision‐making across different ecosystems. It is essential to adopt a holistic approach to ecological modeling to foster sustainable conservation, evaluate diversity, and manage the valuable Morchella resources.

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Development of a Parametric Multi-Material Physics-Informed Neural Network for real-time heat transfer prediction in spherical tokamak divertor under transient heat loads - Habib Ur Rahman; Abid Hussain; Muhammad Ilyas; Lei Li; Khalid Waheed; Manzoor Ahmed (Annals of Nuclear Energy, 2026)

Hematological Modulation and Growth Optimization in Ctenopharyngodon idella through Sorghum Diets supplemented with Chromium Chloride hexahydrate - Gulnaz Zia; Rehana Iqbal; Hamid Manzoor; Muhammad Afzaal; Sumaira Rasul; Muhammad Khalid (Biological Trace Element Research, 2026)

Geographic distribution patterns, population dynamics, and habitat vulnerability of endangered and endemic Trillium govanianum - Syed Waseem Gillani; Mushtaq Ahmad; Muhammad Manzoor; Muhammad Waheed; Raja Waqar Ahmed Khan; Amir Sohail (Environmental Monitoring and Assessment, 2026)

Impact of Aspergillus flavus infection on nutrient composition and storage quality of maize (Zea mays L.) using side needle inoculation - Imran Manzoor; Muhammad Arshad; Rao Muhammad Samran Gul; Ijaz Rasool Noorka; Momina Hussain; Muhammad Sajid; Noorah A. AlKubaisi; Sezai Ercisli; Mohamed S. Elshikh; Abdul Waheed (Journal of Stored Products Research, 2026)

Ambroxol’s Role in PTZ-Induced Anxiety-Like Conditions in Mice: Targeting Neuroinflammation and Oxidative Stress via In Vivo and In Silico Approaches - Hafeeza Zafar Ali; Sarwat Jahan; Laila Ilahi; Sami Siraj; Muhammad Zakria; Najeeb Ullah; Muhammad Ikram; Ashraf Ullah Khan; Manzoor Khan; Fawad Ali Shah; Hafsah Muhammad (Molecular Neurobiology, 2026)

Solid phase microextraction of chlorpyrifos residues in food samples using polyacrylamide@MOF/MXene composite - Sumaira Sabir; Nadeem Raza; Muhammad Hayat; Suryyia Manzoor; Faryal Aftab; Lilia Basilio de Caland; Muhammad Imran Khan; Ahmed Yar; Faisal K. Algethami; Mostafa E. Salem; Anis Ahmad Chaudhary; Muhammad Naeem Ashiq (Food Chemistry, 2025)

Performance enhancement strategies for lithium-based battery electrodes via covalent organic frameworks: A review of recent advances - Waheed Ahmad; Muhammad Tahir; Batoul Bibi; Liang He; Hui Tang; Longbing Qu; Fazal Ul Nisa; Mizna Naseem; Habib Ullah; Iram Abdul Ghafar; Saira Manzoor; Yihao Long; et al. (Chemical Engineering Journal, 2025)

Evaluating Soil Reclamation and Growth Enhancing Potential of Various Types of Biochar with Respect To Rice Crop Cultivated in Saline Sodic Soil - Imran Shehzad; Ghulam Sarwar; Abid Mahmood; Kashf Mehmood; Zuhair Hasnain; Muhammad Zeeshan Manzoor; Danish Ibrar; Saqib Bashir; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (Journal of Soil Science and Plant Nutrition, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Taxonomic significance of pollen micromorphology in family Malvaceae from subtropical ecosystems - Prem Kumar; Mushtaq Ahmad; Syed Waseem Gillani; Muhammad Manzoor; Shazia Sultana; Lixin Zhang; Sokhib Islamov; Jamil Raza (Genetic Resources and Crop Evolution, 2025)

Nutlet micromorphology and systematic implications of genus Nepeta (Lamiaceae): correct taxonomic tool for taxa identifications - Shaista Jabeen; Mushtaq Ahmad; Muhammad Zafar; Shabir Ahmad; Hussain Shah; Ateef Ullah; Syed Waseem Gillani; Muhammad Manzoor; Ashraf M. M. Abdelbacki; Ali M. Sayed (Genetic Resources and Crop Evolution, 2025)

Morpho-palynological evaluation of family Poaceae from arid and semi-arid regions of Pakistan - Bibi Sadia; Mushtaq Ahmad; Wajia Noor; Syed Waseem Gillani; Muhammad Manzoor; Zhiduan Chen; Lixin Zhang; Shazia Sultana; Amir Sohail (Genetic Resources and Crop Evolution, 2025)

Epidemiological, Morphometric, and Genetic Analysis of Pediculus humanus capitis (Head Lice) in Pakistan: Evidence of Regional Diversity and Global Admixture - Muhammad Ilyas; Ayesha Gulzar; Tayyaba Shan; Fazeela Manzoor; Uzma Bibi; Maria Komal; Sabika Firasat; Kiran Afshan (Acta Parasitologica, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Effect of administration of flunixin meglumine on pregnancy and pregnancy loss rates after transfer of low-quality embryos in dromedary camels - Aly Karen; Muhammad Manzoor Ihsan; Muhammad Babar Ihsan; Raza Ur Rahman; Shanmugavelu Muthukumaran; Ahmed Abd-Elfattah (Small Ruminant Research, 2025)

Ultrahigh-porosity peony-like magnesium oxide for the superior adsorption of arsenic (III) and arsenic (V) from aqueous solutions - Ghulam Asghar; Duc Anh Nguyen; Thi Hai Chau Dong; Sumaira Manzoor; Shahid Ali; Muhammad Mansha; Shehzada Muhammad Sajid Jillani; Safyan Akram Khan (Journal of Hazardous Materials, 2025)

Prediction of water status during freeze drying with genetic and whale algorithms of machine learning - Shoaib Younas; Muhammad Ahmad; Ukasha Arqam; Muhammad Sajid Manzoor; Xin Wang; Weijie Li; Caiyun Liu; Zeshan Ali; Muhammad Azeem Sabir; Muhammad Imran (International Journal of Refrigeration, 2025)

Evaluation of growth performance and metabolic efficiency in Labeo rohita fed a sorghum-based diet supplemented with chromium chloride hexahydrate - Gulnaz Zia; Rehana Iqbal; Hamid Manzoor; Muhammad Afzaal; Muhammad Khalid (Aquaculture International, 2025)

Corrigendum to “Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction” [363 (2024) 130919] - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2025)

Functional trait variability and adaptive strategies of Genus Carex along the elevation gradients - Muhammad Waheed; Fahim Arshad; Muhammad Manzoor; Syed Waseem Gillani; Abeer Al-Andal; Kaniz Fatima (Flora, 2025)

Non-small Cell Lung Cancer, Immunotherapy and the Influence of Gut Microbiome - Muhammad Faheem Raziq; Haseeb Manzoor; Masood Ur Rehman Kayani (Current Microbiology, 2025)

Bioenergy by-products enhance the soybean photosynthesis, antioxidant defense, and related gene expression by modulating metal bioavailability in acidic soil - Muhammad Tayyab Sattar; Laiba Qazi; Sumaira Manzoor; Imran Khan; Wenjie Li; Hongju Ma; Fei Shen (Applied Soil Ecology, 2025)

Genomic and taxonomic characterization of Niallia pakistanensis sp. nov. NCCP-28T: a novel antibiotic-resistant and heavy-metal-tolerant bacterium isolated from the legume rhizosphere in Pakistan - Sadia Manzoor; Saira Abbas; Sobia Zulfiqar; Dildar Wu; Hong-Chuan Wang; Wen-Jun Li; Muhammad Arshad; Iftikhar Ahmed (Antonie van Leeuwenhoek, 2025)

Impact of environmental awareness due to the COVID-19 pandemic on consumers’ intention to purchase electric vehicles: the mediating roles of rational and non-rational factors - Muhammad Kashif Javed; Antonio Capaldo; Talat Qadeer; Aqsa Manzoor (Journal of Cleaner Production, 2025)

Flower-like nanoscale Ni(OH)2/MnCO3 electrocatalyst for efficient hydrogen evolution reaction in wide pH range - Zobia Siddique; Salman Noshear Arshad; Muhammad Ali Ehsan; Faryal Aftab; Akhtar Munir; Suryyia Manzoor; Sadia Fatima; Farah Sajjad; Javed Ahmad; Hatice Duran; Senem Çitoğlu (Fuel, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Proline-Induced Changes in Cellular Redox Balance by Modulating Photosystem-II, Photosystem-I, and Activities of Antioxidants in Bread Wheat (Triticum aestivum L.) Under Salinity Stress - Ayesha Khalid; Sarah Ambreen; Aneela Kanwal Shahzadi; Nadeem Hussain; Azra Manzoor; Habib-ur-Rehman Athar; Zafar Ullah Zafar; Muhammad Ashraf (Journal of Plant Growth Regulation, 2025)

Adsorptive Remediation of Cadmium Ions with Modified Plant Straw Using Response Surface Methodology - Aanisa Manzoor Shah; Inayat Mustafa Khan; Rehana Rasool; Tahir A. Sheikh; Muhammad Athar Khaliq; Shaista Nazir; Javid A. Bhat; Yasir Hanif Mir; Rifat un Nissa; Sami Al Obaid; Mohammad Javed Ansari; Shafeeq Ur Rahman (International Journal of Environmental Research, 2025)

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

WITHDRAWN:The effects of soybean protein on lipid profile, bone health in post-menopausal women, comparing healthy vs. hyperlipidemic individuals and safety evaluation in rats. - Muhammad Adnan Manzoor; Adeela Yasmeen; Farhan Saeed; Shumaila Kiran (Food and Humanity, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Unveiling the power of PavGID1s: the critical player in sweet cherry flower bud dormancy release - Xunju Liu; Li Wang; Muhammad Aamir Manzoor; Wanxia Sun; Yan Xu; Muhammad Salman Haider; Zhengxin Lv; Jiyuan Wang; Ruie Liu; Songtao Jiu; Caixi Zhang (Plant Molecular Biology, 2025)

Correction: Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Effects of electromagnetic radiation from offshore wind power on the physiology and behavior of two marine fishes - Peng Xu; Bole Wang; Zhenghao Wang; Renkang Jin; Manzoor Ahmad; Yueyong Shang; Menghong Hu; Fangping Chen; Muhammad Faisal Khalil; Wei Huang; Youji Wang (Marine Pollution Bulletin, 2025)

Development and exploration of casein-based nano-encapsulation of mangiferin for cow milk allergy management and immunomodulation - Muhammad Junaid Anwar; Aneela Hameed; Muhammad Usman Khan; Aimen Mazhar; Hafiz Muhammad Irfan Manzoor (Food Bioscience, 2025)

Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Exploring the taxonomic relevance: foliar epidermal microanatomy of aromatic and medicinal plants within subfamily Nepetoideae - Shaista Jabeen; Muhammad Zafar; Mushtaq Ahmad; Saeedah Musaed Almutairi; Mohamed Soliman Elshikh; Trobjon Makhkamov; Sokhib Islamov; Syed Waseem Gillani; Muhammad Manzoor (Genetic Resources and Crop Evolution, 2025)

Quest for environmental management and sustainability: Evaluating the drivers of territorial and consumption-based carbon emissions in G-20 economies - Muhammad Adnan Bashir; Li Qing; Shahid Manzoor; Shahzad Khan Durrani; Lin Jingting; Nasir Sultan (Journal of Environmental Management, 2025)

Corrigendum to “Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications” [Fuel 357(Part A) (2024) 129688] - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2025)

Corrigendum to “Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices” [Fuel 336 (2023) 127066] - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

Genome-wide identification and expression analysis of CYP450s under various stress treatment in Dendrobium huoshanense - Guohui Li; Xingen Zhang; Yuyue Li; Xilu Zhang; Muhammad Aamir Manzoor; Chuanbo Sun; Cheng Song; Min Zhang (Physiology and Molecular Biology of Plants, 2025)

Disease resistance to tomato yellow leaf curl virus (TYLCV) enhanced by natural plant growth regulators and biopesticide - Sajid Mehmood; Marina Sajid; Tamsal Murtaza; Tanveer Hussain; Rana Naveed Ur Rehman; Muhammad Tahir Akram; Huma Abbas; Khadija Rafiq; Muhammad Kamran; Manzoor Hussain; Muhammad Inam ul Haq; Gull-e-laala Khan (Journal of Plant Diseases and Protection, 2025)

Erratum to: Alleviation of Cadmium Stress on Pollens of Quince Varieties Through Epibrassinolide - Ferhad Muradoğlu; Ömer Beyhan; Taki Demir; Muhammad Arsalan Manzoor; Ferit Sönmez; Hüseyin İrfan Balık (Applied Fruit Science, 2025)

PavSPLs are key regulators of growth, development, and stress response in sweet cherry - Xunju Liu; Wanxia Sun; Haobo Liu; Li Wang; Muhammad Aamir Manzoor; Jiyuan Wang; Songtao Jiu; Caixi Zhang (Plant Science, 2025)

Taxonomic significance of palyno-morphic markers for the delimitation of some Brassicaceous taxa in Balochistan Province (Pakistan) - Wajia Noor; Muhammad Zafar; Mushtaq Ahmad; Bibi Sadia; Syed Waseem Gillani; Muhammad Manzoor; Maria Ameen (Genetic Resources and Crop Evolution, 2025)

Taxonomic implications of petiole microanatomical traits among Asteraceae tribes from arid–semiarid regions of Baluchistan, Pakistan - Bibi Sadia; Mushtaq Ahmad; Muhammad Zafar; Wajia Noor; Muhammad Manzoor; Syed Waseem Gillani; Shazia Sultana (Genetic Resources and Crop Evolution, 2025)

Corrigendum to “Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting” [Fuel 338 (2023) 127313] - Mehar Un Nisa; Soumaya Gouadria; Sara Houda; Karam Jabbour; Sumaira Manzoor; Salma Aman; Muhammad Najam-Ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Nutraceutical tablets: Manufacturing processes, quality assurance, and effects on human health - Muhammad Faisal Manzoor; Sakhawat Riaz; Deepak Kumar Verma; Muhammad Waseem; Gulden Goksen; Anwar Ali; Xin-An Zeng (Food Research International, 2024)

Soy protein-polyphenols conjugates interaction mechanism, characterization, techno-functional and biological properties: An updated review - Muhammad Faisal Manzoor; Xin-An Zeng; Muhammad Waseem; Rabia Siddique; Muhammad Rizwan Javed; Deepak Kumar Verma; Murtaza Ali (Food Chemistry, 2024)

Combined environmental relevant exposure to perfluorooctanoic acid and zinc sulfate enhances apoptosis through binding with endogenous antioxidants in Daphnia magna - Naima Hamid; Muhammad Junaid; Nurhayati Binti Salim; Rakia Manzoor; Ong Meng Chuan (Food and Chemical Toxicology, 2024)

Functional genomics and taxonomic insights into heavy metal tolerant novel bacterium Brevibacterium metallidurans sp. nov. NCCP-602T isolated from tannery effluent in Pakistan - Sadia Manzoor; Saira Abbas; Sobia Zulfiqar; Hong-Chuan Wang; Min Xiao; Wen-Jun Li; Muhammad Arshad; Iftikhar Ahmed (Antonie van Leeuwenhoek, 2024)

Phylogenomic analyses and comparative genomic studies of Thermus strains isolated from Tengchong and Tibet Hot Springs, China - Inam Ullah Khan; Muhammad Saqib; Arshia Amin; Sadia Manzoor; Iftikhar Ahmed; Rui-Rui Liu; Jian-Yu Jiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Biochar and nanoscale silicon synergistically alleviate arsenic toxicity and enhance productivity in chili peppers (Capsicum annuum L.) - Natasha Manzoor; Liaqat Ali; Temoor Ahmad; Muhammad Yahya Khan; Hayssam M. Ali; Ying Liu; Gang Wang (Chemosphere, 2024)

Capturing different modes of hydrogen combustion in a spark-ignition engine using numerical simulations - Muhammad Umair Manzoor; Xinbei Dou; MohammadReza Yosri; Mohsen Talei; Yi Yang (Fuel, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Chronic environmental level exposure to perfluorooctane sulfonate overshadows graphene oxide to induce apoptosis through activation of the ROS-p53-caspase pathway in marine medaka Oryzias melastigma - Nan Xu; Xilin Jiang; Yan Liu; Muhammad Junaid; Manzoor Ahmad; Chunqing Bi; Wenjing Guo; Chen'ao Jiang; Shulin Liu (Chemosphere, 2024)

Analysis of Nutrient and Heavy Metal Contents of Historical Apple Varieties Growing in the Eastern Anatolia Region of Türkiye - Tuba Kırs; Selma Kuru Berk; Muttalip Gündoğdu; Ferhad Muradoğlu; Muhammad Arsalan Manzoor (Applied Fruit Science, 2024)

Recent innovations and emerging technological advances used to improve quality and process of plant-based milk analogs - Taha Mehany; Shahida Anusha Siddiqui; Babatunde Olawoye; Oyekemi Olabisi Popoola; Abdo Hassoun; Muhammad Faisal Manzoor; Sneh Punia Bangar (Critical Reviews in Food Science and Nutrition, 2024)

First report of Pythium aphanidermatum causing coriander damping-off in district Hyderabad, Sindh, Pakistan - Ghulam Sarwar Shah; Jamal-U-Ddin Hajano; Rehana Naz Syed; Muhammad Ibrahim Khaskheli; Manzoor Ali Abro; Muhammad Ali Khanzada; Abdul Mubeen Lodhi (Journal of Plant Pathology, 2024)

The limits to equity in water allocation under scarcity - Wasim Hassan; Talha Manzoor; Abubakr Muhammad (Journal of Hydrology, 2024)

Alleviation of Cadmium Stress on Pollens of Quince Varieties Through Epibrassinolide - Ferhad Muradoğlu; Ömer Beyhan; Taki Demir; Muhammad Arsalan Manzoor; Ferit Sönmez; Hüseyin İrfan Balık (Applied Fruit Science, 2024)

Designing and synthesis of perovskite nanocrystals: a promising wide-spectrum solar light–responsive photocatalyst and lead ion sensor - Nisar Ali; Shakeel Ahmad; Arif Nawaz; Manzoor Khan; Aman Ullah; Muhammad Idrees; Adnan Khan; Wilayat Khan (Environmental Science and Pollution Research, 2024)

Differential involvement of PEBP genes in early flowering of Peucedanum praeruptorum Dunn - Cheng Song; Wenwu Zhang; Muhammad Aamir Manzoor; Irfan Ali Sabir; Haoyu Pan; Luxi Zhang; Yingyu Zhang (Postharvest Biology and Technology, 2024)

Comparative performance of osmotic and thermal driven anaerobic membrane bioreactors for hazardous textile wastewater treatment - Kamran Manzoor; Sher Jamal Khan; Muhammad Saqib Nawaz; Noreddine Ghaffour (Journal of Water Process Engineering, 2024)

Impact of sustainable emerging cold plasma technology on the optical properties of foods - Murtaza Ali; Muhammad Faisal Manzoor; Xin-An Zeng; Afeera Abida; Ume Roobab (Food Bioscience, 2024)

Emerging high intensity ultrasound for soymilk in boosting bioactivity, amino acids release, reducing anti-nutritional factors and allergenicity - Muhammad Hussain; Hao Zhong; Kifayat Hussain; Muhammad Faisal Manzoor; Abdul Qayum; Xiaofeng Liu; Jie Xu; Abid Hussain; Hafiz Muhammad Ahsan; Rongfa Guan (Food Bioscience, 2024)

Electrochemical C-C coupling mediated by novel Sn-SnO2 supported Cu single atoms: The case of CO2 conversion to ethanol - Muhammad Aurang Zeb Gul Sial; Na Guo; Abdul Jalil; Muhammad Abbas; Muhammad Mateen; Sami Ullah; Umair Alam; Zahid Manzoor Bhat; Arshad Hussain; Xingke Cai; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Heavy Metal Stress in Medicinal Plants: Detoxification Mechanisms, Antioxidants, and Implications for Human Health - Muhammad Waheed Riaz; Tong Wu; Quaid Hussain; Fasih Ullah Haider; Weiwei Jiang; Qingsong Shao; Muhammad Aamir Manzoor; Bingcong Xing (Journal of Soil Science and Plant Nutrition, 2024)

Distribution pattern, population structure and habitat geography of Betula utilis subalpine forests of Kashmir region in the western Himalayas: implications for conservation and sustainable management - Muhammad Manzoor; Hamayun Shaheen; Arbaz Attique; Raja Waqar Ahmed Khan; Syed Waseem Gillani; Muhammad Shoaib Khan (Environment, Development and Sustainability, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

Production of manganese telluride-based manganese oxide nano-composite works as a catalyst for effective oxygen evolution reaction - Zainab M. Almarhoon; Karam Jabbour; Sumaira Manzoor; Syed Imran Abbas Shah; Muhammad Faheem Ashiq; Muhammad Yousaf Ur Rehman; Muhammad Fahad Ehsan; Muhammad Najam-ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Exogenous Salicylic Acid Improves Photosynthetic and Antioxidant Capacities and Alleviates Adverse Effects of Cherry Rootstocks Under Salt Stress - Jieming Xu; Yan Xu; Yuxuan Wang; Zhengxin Lv; Xunju Liu; Wanxia Sun; Muhammad Aamir Manzoor; Ruie Liu; Shiping Wang; Songtao Jiu; Caixi Zhang (Journal of Plant Growth Regulation, 2024)

Clubroot (Plasmodiophora brassicae) Suppression Under Biocontrol Agents in Pak choi with Variations in Physiological, Biochemical, and Bacterial Diversity - Shazma Gulzar; Fiza Liaquat; Muhammad Khalid Hameed; Asad Rehman; Muhammad Salman Zahid; Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Yidong Zhang (Journal of Plant Growth Regulation, 2024)

Comprehensive characterization of unscientifically disposed municipal solid waste (MSW) in Kashmir Region, India - Muneeb Farooq; Adhithiya Venkatachalapati Thulasiraman; Zahoor Manzoor; Sachin Tripathi; Farhat Un Nisa; Asif Farooq; Saheem Rasool; Reyaz Hussain Akhoon; Muhammad Yousuf Shah; Khalid Muzamil Gani (Environmental Monitoring and Assessment, 2024)

Heavy metal sequestration from wastewater by metal-organic frameworks: a state-of-the-art review of recent progress - Ali Shaan Manzoor Ghumman; Rashid Shamsuddin; Lailatul Qomariyah; Jun Wei Lim; Abdul Sami; Muhammad Ayoub (Environmental Science and Pollution Research, 2024)

Horticulture crop under pressure: Unraveling the impact of climate change on nutrition and fruit cracking - Muhammad Aamir Manzoor; Yan Xu; Zhengxin lv; Jieming Xu; Iftikhar Hussain Shah; Irfan Ali Sabir; Yuxuan Wang; Wanxia Sun; Xunju Liu; Li Wang; Ruie Liu; Songtao Jiu; et al. (Journal of Environmental Management, 2024)

Comparative genomics of N-acetyl-5-methoxytryptamine members in four Prunus species with insights into bud dormancy and abiotic stress responses in Prunus avium - Muhammad Aamir Manzoor; Yan Xu; Zhengxin lv; Jieming Xu; Yuxuan Wang; Wanxia Sun; Xunju Liu; Li Wang; Muhammad Abdullah; Ruie Liu; Songtao Jiu; Caixi Zhang (Plant Cell Reports, 2024)

Genome-wide identification and expression analysis of TIFY genes under MeJA, cold and PEG-induced drought stress treatment in Dendrobium huoshanense - Guohui Li; Muhammad Aamir Manzoor; Rui Chen; Yingyu Zhang; Cheng Song (Physiology and Molecular Biology of Plants, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Natural deep eutectic solvent: A promising eco-friendly food bio-inspired antifreezing - Xue Li; Jia-Ying Li; Muhammad Faisal Manzoor; Qiu-Ya Lin; Jia-ling Shen; Lan Liao; Xin-An Zeng (Food Chemistry, 2024)

Metagenomic and biochemical analyses reveal the potential of silicon to alleviate arsenic toxicity in rice (Oryza sativa L.) - Temoor Ahmed; Junning Guo; Muhammad Noman; Luqiong Lv; Natasha Manzoor; Xingjiang Qi; Bin Li (Environmental Pollution, 2024)

Comprehensive review: Effects of climate change and greenhouse gases emission relevance to environmental stress on horticultural crops and management - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Wu Jinhui; Xuyang Li; Muhammad Khalid Hameed; Asad Rehaman; Pengli Li; Yidong Zhang; Qingliang Niu; Liying Chang (Journal of Environmental Management, 2024)

Facile synthesis of CuAl2O4/rGO nanocomposite via the hydrothermal method for supercapacitor applications - Shahzaib Khan; Muhammad Usman; Muhammad Abdullah; Muhammad Suleman Waheed; Muhammad Faheem Ashiq; Muhammad Ishfaq Ahmad; Abdulnasser M. Karami; Muhammad Fahad Ehsan; Sumaira Manzoor; Muhammad Naeem Ashiq (Fuel, 2024)

From biodiversity hotspot to conservation hotspot: assessing distribution, population structure, associated flora and habitat geography of threatened Himalayan Yew in temperate forest ecosystems of Kashmir - Hamayun Shaheen; Arbaz Attique; Malik Talha Riaz; Muhammad Manzoor; Raja Waqar Ahmed Khan; Muhammad Tayyib Riaz (Biodiversity and Conservation, 2024)

Field‐scale measurements of soil physico‐chemical profiles of the Potohar region in the Indus basin of Pakistan - Manzoor Ahmad Malik; Muhammad Ashraf (Irrigation and Drainage, 2024)
Soil physico‐chemical properties are important for best management practices. We measured infiltration, bulk density, texture, water retention and chemical profiles from the surface to 1.0 m and lithology to 50 m depths at 30 sites. The infiltration data were fitted to the cumulative and infiltration rate models of Philip and Horton. The same sites were used for water retention, physico‐chemical properties and lithological assessment. The cumulative models fit persistently better than their infiltration rate forms. The Horton cumulative model fitted statistically better than the corresponding Philip model. The dominant steady‐state infiltration rates were 15–30 and 30–45 mm h −1 over the entire profile. Sandy loam, loam and silt loam were the dominant soils. The percentages of sandy loam decreased, whereas silt loam increased, with depth. Water retention parameters and lithological strata were diverse and in harmony with physiography. Soil organic matter varied up to 2.5%. No sodicity or salinity was detected except in sparse saline seeps. The central tendency and extrema of the measured parameters were compatible with the literature, and the CVs of the soil hydraulic parameters were greater than those of the physical parameters. Comprehensive data are presented, which will serve as an important reference for regional and global repositories.

Fucoidan-based nanomaterial and its multifunctional role for pharmaceutical and biomedical applications - Muhammad Waheed Iqbal; Tahreem Riaz; Shahid Mahmood; Muhammad Bilal; Muhammad Faisal Manzoor; Sarmad Ahmad Qamar; Xianghui Qi (Critical Reviews in Food Science and Nutrition, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Scalable synthesis of MOF-derived Nd2O3@C and V2O5@C nanohybrid: Efficient electrocatalyst for OER in alkaline medium - Tauseef Munawar; Ambreen Bashir; Muhammad Shahid Nadeem; Faisal Mukhtar; Sumaira Manzoor; Muhammad Naeem Ashiq; Shoukat Alim Khan; Muammer Koc; Faisal Iqbal (Fuel, 2024)

Magnetic solid phase extraction of aminoglycosides residue in chicken egg samples using Fe3O4-GO-Agarose-Chitosan composite - Muhammad Sajjad; Rasmiah Almufarij; Zeeshan Ali; Muhammad Sajid; Nadeem Raza; Suryyia Manzoor; Muhammad Hayat; Ehab A. Abdelrahman (Food Chemistry, 2024)

An integrated assessment of ecological and human health risks of per- and polyfluoroalkyl substances through toxicity prediction approaches - Naima Hamid; Muhammad Junaid; Rakia Manzoor; Marriya Sultan; Ong Meng Chuan; Jun Wang (Science of The Total Environment, 2023)

Enhanced lead phytoextraction and soil health restoration through exogenous supply of organic ligands: Geochemical modeling” - Maria Manzoor; Muhammad Shafiq; Iram Gul; Usman Rauf Kamboh; Dong-Xing Guan; Abdulrahman Ali Alazba; Sven Tomforde; Muhammad Arshad (Journal of Environmental Management, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Molecular characterization of lumpy skin disease virus from recent outbreaks in Pakistan - Shumaila Manzoor; Muhammad Abubakar; Aziz Ul-Rahman; Zainab Syed; Khurshid Ahmad; Muhammad Afzal (Archives of Virology, 2023)

Petrophysical properties evaluation and reservoir characterization of a giant gas field: Bangladesh case study - Mehedi Hasan; Bineta Mondol; Litao Chen; Muhammad Wajid Manzoor (Arabian Journal of Geosciences, 2023)

Analysis of coumarin content and key enzyme genes expression involved in coumarin biosynthesis from Peucedanum praeruptorum Dunn at different stages - Peipei Wei; Yaobiqi Li; Cheng Song; Muhammad Aamir Manzoor; Jun Dai; Qihui Yin; Yanmei Zhang; Bangxing Han (Acta Physiologiae Plantarum, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Evaluating dye recovery and reusability potential from dyebath effluent using forward osmosis membranes for minimum liquid discharge - Maria Yasmeen; Muhammad Saqib Nawaz; Kamran Manzoor; Sher Jamal Khan; Noreddine Ghaffour (Chemosphere, 2023)

Biogenic silicon nanoparticles mitigate cadmium (Cd) toxicity in rapeseed (Brassica napus L.) by modulating the cellular oxidative stress metabolism and reducing Cd translocation - Temoor Ahmed; Hafiza Ayesha Masood; Muhammad Noman; Arwa Abdulkreem AL-Huqail; Suliman MS Alghanem; Muhammad Munem Khan; Sher Muhammad; Natasha Manzoor; Muhammad Rizwan; Xingjiang Qi; Amany H.A. Abeed; Bin Li (Journal of Hazardous Materials, 2023)

Unraveling the potential of microbes in decomposition of organic matter and release of carbon in the ecosystem - Taqi Raza; Muhammad Farhan Qadir; Khuram Shehzad Khan; Neal S. Eash; Muhammad Yousuf; Sumanta Chatterjee; Rabia Manzoor; Sana ur Rehman; Joel Nathaniel Oetting (Journal of Environmental Management, 2023)

Improving microbial and lipid oxidative stability of cheddar cheese using cricket protein hydrolysates pre-treated with microwave and ultrasonication - Aunzar B. Lone; Hina F. Bhat; Sunil Kumar; Mehnaza Manzoor; Abdo Hassoun; Abderrahmane Aït-Kaddour; Tanyaradzwa E. Mungure; Rana Muhammad Aadil; Zuhaib F. Bhat (Food Chemistry, 2023)

Assessing pyrolysis performance and product evolution of various medical wastes based on model-free and TG-FTIR-MS methods - Fahim Ullah; Guozhao Ji; Lei Zhang; Muhammad Irfan; Zegang Fu; Zakia Manzoor; Aimin Li (Chemical Engineering Journal, 2023)

Green technology for water scarcity: An entrepreneurial business may bring transformation in water management practices - Muhammad Siddique; Manzoor A. Sanjrani; Keenjhar Rani (Irrigation and Drainage, 2023)
Despite the contributions of modern business practices to environmentally sustainable transformation, there is not enough information on different types of green technologies and their applications. Therefore, it is essential to identify and classify business models that focus on the management practices of green technology. While the literature on green technology business models has received increasing attention over the last decade, interdisciplinary research into this growing phenomenon is still in its infancy and fragmented. The study focuses on the need for green technology for water management worldwide. Such management practices for green technology represent a research gap in the study area because no one has worked in this field before. There should be research to address people's management practices of green entrepreneurial business. The literature highlights that the issue of water crises may be minimized with the management practices of green entrepreneurial business and by applying global green water treatment techniques. The authors believe that this study would be very beneficial for future research on policymaking based on management practices of green technology that promote environmental sustainability through a green business environment.

Co-application of copper oxide nanoparticles and Trichoderma harzianum with physiological, enzymatic and ultrastructural responses for the mitigation of salt stress - Iftikhar Hussain Shah; Irfan Ali Sabir; Asad Rehman; Muhammad Khalid Hameed; Gadah Albashar; Muhammad Aamir Manzoor; Awais Shakoor (Chemosphere, 2023)

Smart reprogramming of jujube germplasm against salinity tolerance through molecular tools - Meryam Manzoor; Safina Naz; Hafiza Muniba Din Muhammad; Riaz Ahmad (Functional & Integrative Genomics, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Environmental sustainable: Biogenic copper oxide nanoparticles as nano-pesticides for investigating bioactivities against phytopathogens - Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Irfan Ali Sabir; Ajaz Ahmad; Gadah Albasher; Afzal Ahmed Dar; Muhammad Ahsan Altaf; Awais Shakoor (Environmental Research, 2023)

Increased health risk assessment in different vegetables grown under untreated sewerage irrigation regime due to higher heavy metals accumulation - Zeshan Hassan; Ammara Hassan; Muhaiman Riaz; Azhar Abbas Khan; Sami Ul-Allah; Umbreen Shehzad; Muhammad Khurshid; Ali Bakhsh; Jawad Munawar Shah; Zahid Manzoor (Environmental Science and Pollution Research, 2023)

Effects of melatonin and Trichoderma harzianum on pak choi yield, chlorophyll contents and antioxidant defense system under clubroot disease - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Iftikhar Hussain Shah; Asad Rehman; Muhammad Khalid Hameed; Samiah Arif; Xuanwei Zhou; Yidong Zhang (South African Journal of Botany, 2023)

Normal and knocking combustion of hydrogen: A numerical study - Muhammad Umair Manzoor; MohammadReza Yosri; Mohsen Talei; Farzad Poursadegh; Yi Yang; Michael Brear (Fuel, 2023)

Design of tropinium-functionalized anion exchange membranes for acid recovery via diffusion dialysis process - Muhammad Imran Khan; Abdallah Shanableh; Suryyia Manzoor; Javier Fernandez; Sameh M. Osman; Rafael Luque (Environmental Research, 2023)

Segmentation of digital rock images using texture analysis and deep network - Shahzad Manzoor; Tehreem Qasim; Naeem Bhatti; Muhammad Zia (Arabian Journal of Geosciences, 2023)

Development of Mn-MOF/CuO composites as platform for efficient electrocatalytic OER - Bushra Shabbir; Nidhal Drissi; Karam Jabbour; Abdelaziz Gassoumi; F.F. Alharbi; Sumaira Manzoor; Muhammad Faheem Ashiq; H.A. Alburaih; Muhammad Fahad Ehsan; Muhammad Naeem Ashiq (Fuel, 2023)

Endophytic bacterial diversity by 16S rRNA gene sequencing of Pak choi roots under fluazinam, Trichoderma harzianum, and Sophora flavescens inoculation - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Muhammad Salman Zahid; Samiah Arif; Xuanwei Zhou; Yidong Zhang (Functional & Integrative Genomics, 2023)

Metallic nanoparticles photodegraded antibiotics and co-application improved wheat growth and nutritional quality through stress alleviation - Anum Amin; Maria Manzoor; Muhammad Wajahat Ramay; Ali Hassan; Kiran Hina; Asad Syed; Ali H. Bahkali; Muhammad Arshad (Chemosphere, 2023)

Application of QPPO/PVA based commercial anion exchange membrane as an outstanding adsorbent for the removal of Eosin-B dye from wastewaters - Muhammad Imran Khan; Abdallah Shanableh; Akram M. Alfantazi; Mushtaq Hussain Lashari; Suryyia Manzoor; Ramsha Anwer; Nosheen Farooq; Farid A. Harraz; Mabkhoot Alsaiari; M. Faisal (Chemosphere, 2023)

Molecularly imprinted ormosil as a sorbent for targeted dispersive solid phase micro extraction of pyriproxyfen from strawberry samples - Muhammad Hayat; Suryyia Manzoor; Hina Raza; Muhammad Imran Khan; Abdallah Shanableh; Muhammad Sajid; Tahani Mazyad Almutairi; Rafael Luque (Chemosphere, 2023)

Modification in cellulose films through ascent cold plasma treatment and polymerization for food products packaging - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Rana Muhammad Aadil; Muhammad Faisal Manzoor; Jun-Hu Cheng (Trends in Food Science & Technology, 2023)

Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting - Mehar Un Nisa; Soumaya Gouadria; Sara Houda; Karam Jabbour; Sumaira Manzoor; Salma Aman; Muhammad Najam-Ul-Haq; Muhammad Naeem Ashiq (Fuel, 2023)

Natural pigments: Anthocyanins, carotenoids, chlorophylls, and betalains as colorants in food products - Brera Ghulam Nabi; Kinza Mukhtar; Waqar Ahmed; Muhammad Faisal Manzoor; Muhammad Modassar Ali Nawaz Ranjha; Marek Kieliszek; Zuhaib F. Bhat; Rana Muhammad Aadil (Food Bioscience, 2023)

Expression of pro-inflammatory cytokines (IL-6 & IL-18) exacerbate the risk of diabetic nephropathy in the Pakistani population - Maha Maqsood; Saima Sharif; Shagufta Naz; Tasnim Farasat; Farkhanda Manzoor; Maqsood Cheema; Muhammad Saqib (Molecular Biology Reports, 2023)

Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2023)

Development of CuO/CuS/MnO2 ternary nanocomposite for visible light-induced photocatalytic degradation of methylene blue - Muhammad Abdullah; Peter John; Muhammad Naeem Ashiq; Sumaira Manzoor; Muhammad Ishfaq Ghori; Mehar Un Nisa; Abdul Ghafoor Abid; Kashif Younas Butt; Saeed Ahmed (Nanotechnology for Environmental Engineering, 2023)

Phytotoxic effects of chemically synthesized copper oxide nanoparticles induce physiological, biochemical, and ultrastructural changes in Cucumis melo - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fiza Liaquat; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Science and Pollution Research, 2023)

Tumor micro-environment sensitive release of doxorubicin through chitosan based polymeric nanoparticles: An in-vitro study - Muhammad Usman Akram; Naseem Abbas; Muhammad Farman; Suryyia Manzoor; Muhammad Imran Khan; Sameh M. Osman; Rafael Luque; Abdallah Shanableh (Chemosphere, 2023)

Defective nickel zirconium oxide mesoporous bifunctional electrocatalyst for oxygen evolution reaction and overall water splitting - Maira Sadaqat; Sumaira Manzoor; Salma Aman; Laraib Nisar; Muhammad Najam-Ul-Haq; Afzal Shah; Ahmed M. Shawky; H. Elhosiny Ali; Muhammad Naeem Ashiq; T.A. Taha (Fuel, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

Experimental design by response surface methodology for efficient cefixime uptake from hospital effluents using anion exchange membrane - Muhammad Ali Khan; Nadeem Raza; Suryyia Manzoor; Ramsha Shuja; Hina Raza; Muhammad Imran Khan; Mudassar Azam; Abdallah Shanableh (Chemosphere, 2023)

Nickel-based nitrodopamine MOF and its derived composites functionalized with multi-walled carbon nanotubes for efficient OER applications - Sonia Kiran; Ghazala Yasmeen; Zahid Shafiq; Amir Abbas; Sumaira Manzoor; Dilshad Hussain; Rami Adel Pashameah; Eman Alzahrani; Abdullah K. Alanazi; Muhammad Naeem Ashiq (Fuel, 2023)

Nitrogen-rich three-dimensional metal-organic framework microrods as an efficient electrocatalyst for oxygen evolution reaction and supercapacitor applications - Muhammad Imran Anwar; Sumaira Manzoor; Limin Ma; Muhammad Asad; Wenhua Zhang; Zahid Shafiq; Muhammad Naeem Ashiq; Guang Yang (Fuel, 2023)

Downregulation of NF-κB activation pathways using essential oil derived from Citrus pseudolimon: Anticancer and anti-inflammatory potential - Arfaa Sajid; Qaisar Manzoor; Anam Sajid; Arif Nazir; Muhammad Arsalan Mumtaz; Najum Fatima; Samar Zuhair Alshawwa; Munawar Iqbal; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Phytoaccumulation of cadmium by Pelargonium × hortorum — tolerance and metal recovery - Iram Gul; Maria Manzoor; Imran Ahmad; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2022)

A green and environmental sustainable approach to synthesis the Mn oxide nanomaterial from Punica granatum leaf extracts and its in vitro biological applications - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Monitoring and Assessment, 2022)

Mixing tannery effluent had fertilizing effect on growth, nutrient accumulation, and photosynthetic capacity of some cucurbitaceous vegetables: A little help from foe - Muhammad Zaheer; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Hussan Bano; Misbah Amir; Ayesha Khalid; Hamid Manzoor; Muhammad Javed; Muhammad Iqbal; Chukwuma C. Ogbaga; Muhammad Kamran Qureshi (Environmental Science and Pollution Research, 2022)

A comparative analysis of renewable and non-renewable energy generation to relegate CO2 emissions and general costs in household systems - Mudassar Hussain; Manzoor Sultan; Faiza Uzma; Cheng Longsheng; Muhammad Yousaf Malik; Abdul Rahman Butt; Aqsa Sajjad; Ijaz Younis; Muhammad Imran (Environmental Science and Pollution Research, 2022)

Photosynthetic Efficiency and Antioxidant Defense Potential are Key Players in Inducing Drought Tolerance in Transgenic Tobacco Plants Over-Expressing AVP1 - Hamid Manzoor; Muhammad Shahzad Anjam; Fozia Saeed; Sumaira Rasul; Saira Yousaf; Ayesha Kirn; Muhammad Kamran Qureshi; Zafar Ullah Zafar; Muhammad Ashraf; Habib-ur-Rehman Athar (Journal of Plant Growth Regulation, 2022)

Do environmental technology and banking sector development matter for green growth? Evidence from top-polluted economies - Manzoor Ahmed; Muhammad Hafeez; Muhammad Abdul Kaium; Sana Ullah; Haseeb Ahmad (Environmental Science and Pollution Research, 2022)

Impact assessment of drought monitoring events and vegetation dynamics based on multi-satellite remote sensing data over Pakistan - Shahzad Ali; Abdul Basit; Jian Ni; Manzoor; Fahim Ullah Khan; Muhammad Sajid; Muhammad Umair; Tyan Alice Makanda (Environmental Science and Pollution Research, 2022)

Effect of co-fermentation system with isolated new yeasts on soymilk: microbiological, physicochemical, rheological, aromatic, and sensory characterizations - Sameh A. Korma; Li Li; Mohamed Ghamry; Qiyang Zhou; Peipei An; Khaled A. E. Abdrabo; Muhammad Faisal Manzoor; Abdur Rehman; Sobia Niazi; Ilaria Cacciotti (Brazilian Journal of Microbiology, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Genome-wide identification and comparative analysis of MATE gene family in Cucurbitaceae species and their regulatory role in melon (Cucumis melo) under salt stress - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fazal Haq; Samiah Arif; Muhammad Abdullah; Qingliang Niu; Yidong Zhang (Horticulture, Environment, and Biotechnology, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Enhancing wheat-flour safety by detecting and controlling red flour beetle Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) - Fuqiang Gao; Yajing Qi; Alkassoumi Hassane Hamadou; Jiyao Zhang; Muhammad Faisal Manzoor; Qin Guo; Bin Xu (Journal of Consumer Protection and Food Safety, 2022)

Feeding niche overlap between native and alien fishes in Swat River, Khyber Pakhtunkhwa, Pakistan - Amir Said; Muhammad Imran; Muhammad Tahir Waseem; Abdul Majid Khan; Noman Khalique; Ghulam Sarwar; Rana Manzoor Ahmad (Environmental Biology of Fishes, 2022)

A pathway toward future sustainability: Assessing the influence of innovation shocks on CO2 emissions in developing economies - Zhu Weimin; Muhammad Zubair Chishti; Abdul Rehman; Manzoor Ahmad (Environment, Development and Sustainability, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

A Novel Visual-Range Sea Image Dataset for Sea Horizon Line Detection in Changing Maritime Scenes - Manzoor Ahmed Hashmani; Muhammad Umair (Journal of Marine Science and Engineering, 2022)
Sea horizon line (SHL) detection plays a pivotal role in the computational performance improvement of computer applications for the maritime environment by dividing the image into sea and sky regions. This division isolates the region of interest and reduces the computational cost of further processing. Testing and performance evaluation of SHL detection methods require a robust image dataset covering the maritime environment’s features at different geographical, seasonal, and maritime conditions. However, publicly available maritime image datasets are developed under a limited environment with slight-to-moderate variations in maritime features. This article proposes a novel sea image dataset that fills this gap by incorporating various geographical, seasonal, and maritime features. Across West Malaysia, one offshore and four geographically separated onshore locations were selected. On ten different occasions, field observations were recorded using a visual-range optical sensor and weather station. The data collection experiments were conducted between February 2020 until April 2021. The collected data were preprocessed and SHL images were selected based on their high feature diversity. Manual SHL annotation was applied on images, and a ground truth matrix was generated, which serves as a performance benchmark for SHL detection methods. As a result, the dataset presents 2673 high-definition (1920 × 1080 pixels) RGB images having a combination of 36 different geographical, seasonal, and maritime features to test and evaluate computer vision-based SHL detection methods.

Correction to: Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

Water resources of Balochistan, Pakistan—a review - Malik Muhammad Akhtar; Abida Dost Mohammad; Muhsan Ehsan; Rabia Akhtar; Jalil ur Rehman; Zaira Manzoor (Arabian Journal of Geosciences, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

Systematic study of the new remains of Propotamochoerus hysudricus (Suidae, Mammalia) from the Late Miocene–Early Pliocene of Middle Siwaliks (Pakistan) - Sadaf Aslam; Abdul Majid Khan; Rana Manzoor Ahmad; Ayesha Iqbal; Muhammad Tahir Waseem (Arabian Journal of Geosciences, 2021)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Induction of Modern Water Distribution Systems in Punjab of Indo-Pak Subcontinent, South Asia During Late Nineteenth Century by British Government - Muhammad Sohail; Suryyia Manzoor (Sustainable Water Resources Management, 2020)

Influence of early rearing environment on water-borne cortisol and expression of stress-related genes in grass carp (Ctenopharyngodon idella) - Mahmood ul Hassan Murtaza; Amina Zuberi; Muhammad Ahmad; Imrana Amir; Muhammad Kamran; Manzoor Ahmad (Molecular Biology Reports, 2020)

Phenolic Profile and Thermal Stability of Monovarietal Extra Virgin Olive Oils Based on Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Azhar Iqbal; Babar Manzoor Atta; Rahat Ullah; Muhammad Bilal Khan (Journal of Fluorescence, 2020)

Application of Fluorescence Spectroscopy in Wheat Crop: Early Disease Detection and Associated Molecular Changes - Babar Manzoor Atta; Muhammad Saleem; Hina Ali; Muhammad Bilal; Muhammad Fayyaz (Journal of Fluorescence, 2020)

Systematic and paleoecological study of the new remains of Brachypotherium (Rhinocerotidae) from the Middle Miocene Siwaliks (Pakistan) - Amtur Rafeh; Abdul Majid Khan; Rana Manzoor Ahmad; Mudassar Iqbal; Muhammad Akhtar (Arabian Journal of Geosciences, 2020)

Achromobacter sp. FB-14 harboring ACC deaminase activity augmented rice growth by upregulating the expression of stress-responsive CIPK genes under salinity stress - Muhammad Shahid; Asad Ali Shah; Farwa Basit; Muhammad Noman; Muhammad Zubair; Temoor Ahmed; Tahir Naqqash; Irfan Manzoor; Awais Maqsood (Brazilian Journal of Microbiology, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Detection of antibodies to peste-des-petits-ruminants virus in the semi-domesticated yak - Muhammad Abubakar; Nosirjon Sattorov; Shumaila Manzoor; Ehtisham ul Haq Khan; Manzoor Hussain; Aamir Bin Zahur; Muhammad Afzal; Jonas Johansson Wensman (European Journal of Wildlife Research, 2019)
Peste des petits ruminants (PPR) is a highly contagious and acute viral disease of small ruminants. Occasionally, PPR can affect wildlife with devastating results, such as the recent outbreaks in Mongolian saiga. The yak ( Bos grunniens and Bos mutus ) is a large ruminant found throughout the Himalayan region of south Central Asia, the Tibetan Plateau and as far north as Mongolia and Russia. In Pakistan, yaks are confined to the high plateau of the Northern Areas, from Gilgit to the valley of Ladakh. In Tajikistan, yaks are present in districts in the north, east and southeast of the country. Commonly, yak intermingle with domestic animals during winter when mountainous summer pastures are covered with snow, and with wildlife during summer pastures. PPR is considered endemic in sheep and goats in Pakistan and Tajikistan. In this study, we investigated the potential presence of antibodies to peste-des-petits-ruminants virus (PPRV) in yak populations using ELISA. A total of 250 (Pakistan) and 85 (Tajikistan) serum samples of healthy yaks were collected. None of the Tajik yaks were seropositive (95% confidence interval (CI) 0.0–4.2%), while 23 of 250 (9.2%; 95% CI 5.9–13.5%) yaks sampled in Pakistan were found positive. Whether PPRV is continuously circulating among yaks or seroconversion reflects spill-over from outbreaks of PPR in domestic animals remains unknown. Due to the herding practices, yak might transmit PPR from domestic to wild ruminants. Differences in contacts between yaks and domestic animals in Pakistan and Tajikistan, or the low sample size, could explain that no Tajik yaks were seropositive.

Total retail goods consumption, industry structure, urban population growth and pollution intensity: an application of panel data analysis for China - Zeeshan Khan; Muhammad Shahbaz; Manzoor Ahmad; Fazli Rabbi; Yang Siqun (Environmental Science and Pollution Research, 2019)

The nexus of fiscal policy instruments and environmental degradation in China - Peng Yuelan; Muhammad Waqas Akbar; Muhammad Hafeez; Manzoor Ahmad; Zeenat Zia; Sana Ullah (Environmental Science and Pollution Research, 2019)

Fungi-assisted phytoextraction of lead: tolerance, plant growth–promoting activities and phytoavailability - Maria Manzoor; Iram Gul; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2019)

Comparative effectiveness of organic and inorganic amendments on cadmium bioavailability and uptake by Pelargonium hortorum - Iram Gul; Maria Manzoor; Nosheen Hashim; Khurram Yaqoob; Jean Kallerhoff; Muhammad Arshad (Journal of Soils and Sediments, 2019)

Genetic polymorphism in association with susceptibility to tuberculosis: a study in a Pakistani population - AsmaGul Naz; Muhammad Assad Aslam; Abrar Ul Haq Khan; Sumaira Rasul; Hamid Manzoor; Rehana Iqbal; Ahmed Shehzad; Muhammad Ali (Brazilian Journal of Microbiology, 2019)

Thermal Effects on Biochemical Signatures of UHT, Pasteurized and Domestically Boiled Buffalo Milk Detected by Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Saleem; Rahat Ullah; Saranjam Khan; Babar Manzoor Atta; Muhammad Bilal (Journal of Fluorescence, 2019)

IL-22 in hepatocyte’s survival of Pakistani patients with end stage liver disease: an insight into IL 22 mediated hepato-regenerative pathway - Muhammad Saalim; Saleha Resham; Sobia Manzoor; Hassam Ahmad; Tariq Ali Bangash; Amir Latif; Shahla Jaleel (Molecular Biology Reports, 2019)

Analysis of the resistance of Gossypium herbaceum to cotton leaf curl kokhran virus strain burewala and cotton leaf curl multan betasatellite - Rahim Ullah; Khalid Pervaiz Akhtar; Peter Moffett; Tawaf Ali Shah; Manzoor Hussain; Muhammad Kashif Riaz Khan; Shahid Mansoor; Muhammad Saeed (Journal of Plant Pathology, 2018)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Does finance affect environmental degradation: evidence from One Belt and One Road Initiative region? - Muhammad Hafeez; Yuan Chunhui; David Strohmaier; Manzoor Ahmed; Liu Jie (Environmental Science and Pollution Research, 2018)

Distribution of IL28B and IL10 polymorphisms as genetic predictors of treatment response in Pakistani HCV genotype 3 patients - Humaira Naeemi; Rabia Aslam; Syed Mohsin Raza; Muhammad Aiman Shahzad; Shagufta Naz; Sobia Manzoor; Saba Khaliq (Archives of Virology, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Osteopontin gene polymorphism association with milk traits and its expression analysis in milk of riverine buffalo - Sidra Manzoor; Asif Nadeem; Javed Maryam; Abu Saeed Hashmi; Muhammad Imran; Masroor Ellahi Babar (Tropical Animal Health and Production, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Influence of sub-lethal crude oil concentration on growth, water relations and photosynthetic capacity of maize (Zea mays L.) plants - Habib-ur-Rehman Athar; Sarah Ambreen; Muhammad Javed; Mehwish Hina; Sumaira Rasul; Zafar Ullah Zafar; Hamid Manzoor; Chukwuma C. Ogbaga; Muhammad Afzal; Fahad Al-Qurainy; Muhammad Ashraf (Environmental Science and Pollution Research, 2016)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Cytotoxic, antibacterial and antioxidant activities of extracts of the bark of Melia azedarach (China Berry) - Muhammad Zahoor; Manzoor Ahmed; Sumaira Naz; Musarrat Ayaz (Natural Product Research, 2015)

An appraisal on the occurrence of foot-and-mouth disease virus serotypes in cattle and buffaloes, Pakistan - Muhammad Abubakar; Ehtisham-ul-Haq Khan; Muhammad Javed Arshed; Jose Gonzales; Giancarlo Ferrari; Manzoor Hussain; Qurban Ali (Archives of Virology, 2015)

A new rosane-type diterpenoid from Stachys parviflora and its density functional theory studies - Umar Farooq; Khurshid Ayub; Muhammad Ali Hashmi; Rizwana Sarwar; Afsar Khan; Mumtaz Ali; Manzoor Ahmad; Ajmal Khan (Natural Product Research, 2015)

Exploitation of synthetic-derived wheats through osmotic stress responses for drought tolerance improvement - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Manzoor Ahmad; Hassan Sher; Sammer Fatima; Alvina Gul Kazi; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2014)

Erratum to: Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

A distinct strain of chickpea chlorotic dwarf virus (genus Mastrevirus, family Geminiviridae) identified in cotton plants affected by leaf curl disease - Muhammad Tariq Manzoor; Muhammad Ilyas; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid; Rob W. Briddon (Archives of Virology, 2014)

Current and future therapies for hepatitis C virus infection: from viral proteins to host targets - Muhammad Imran; Sobia Manzoor; Nasir Mahmood Khattak; Madiha Khalid; Qazi Laeeque Ahmed; Fahed Parvaiz; Muqddas Tariq; Javed Ashraf; Waseem Ashraf; Sikandar Azam; Muhammad Ashraf (Archives of Virology, 2014)

Synthesis and biological evaluation of some N4-substituted 5-nitroisatin-3-thiosemicarbazones - Humayun Pervez; Nazia Manzoor; Muhammad Yaqub; Faiz-ul-Hassan Nasim; Khalid M. Khan (Medicinal Chemistry Research, 2012)

Antimalarial and free radical scavenging activities of rhizomes of Polygonatum verticillatum supported by isolated metabolites - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Inamullah Khan; Manzoor Ahmad; Naveed Muhammad; Afsar Khan (Medicinal Chemistry Research, 2012)

Bovine hypodermosis—a global aspect - Murtaz-ul Hassan; Muhammad Nisar Khan; Muhammad Abubakar; Hafiz Muhammad Waheed; Zafar Iqbal; Manzoor Hussain (Tropical Animal Health and Production, 2010)

Peste des petits ruminants virus (PPRV) infection; Its association with species, seasonal variations and geography - Muhammad Abubakar; Syed Muhammad Jamal; Muhammad Javed Arshed; Manzoor Hussain; Qurban Ali (Tropical Animal Health and Production, 2009)